The effect of strengthening the literacy movement in natural and social sciences (IPAS) learning on improving students' scientific literacy and critical thinking skills - Diah Susilowati; Bagus Ardi Saputro; Agus Sutono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Literacy is an essential 21st-century skill, encompassing critical thinking and scientific literacy as key elements in science education. This study analyzes the effect of strengthening the School Literacy Movement (Gerakan Literasi Sekolah or GLS) in Natural and Social Sciences (IPAS) learning on students' scientific literacy and critical thinking skills. The study employed a quasi-experimental design involving 41 fourth-grade students from SDN 01 Wanarejan, divided into experimental and control classes. The experimental class received a systematic integration of the School Literacy Movement (GLS) in Natural and Social Sciences (IPAS) learning. The findings showed that integrating GLS into IPAS learning significantly improved students' scientific literacy and critical thinking skills. This study concludes that a well-planned integration of GLS in IPAS learning can support the development of students' higher-order thinking skills.